2012
DOI: 10.1111/j.1751-1097.2012.01110.x
|View full text |Cite
|
Sign up to set email alerts
|

Hairless and NFκB Form a Positive Feedback Loop After UVB and TNFα Stimulation

Abstract: Hairless (HR) is a nuclear protein with corepressor activity whose exact function in the skin remains to be determined. Mutations in both human and mouse Hairless lead to hair loss accompanied by the appearance of papules, a disorder called atrichia with papular lesions. Furthermore, mice with mutations in HR are known to have a higher susceptibility to ultraviolet radiation-induced tumorigenesis, suggesting that HR plays a crucial role in the epidermal UVB response. Using normal human keratinocytes (NHKs) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…NFκB has long been known to play a role in UVB induced tumorigenesis and forms a nexus of proliferative and apoptotic pathways; additionally, our previous work shows that HR regulates NFκB in vitro [29]. We therefore theorized that Hr and NFκB may be mechanistically related in a similar fashion in vivo .…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…NFκB has long been known to play a role in UVB induced tumorigenesis and forms a nexus of proliferative and apoptotic pathways; additionally, our previous work shows that HR regulates NFκB in vitro [29]. We therefore theorized that Hr and NFκB may be mechanistically related in a similar fashion in vivo .…”
Section: Resultsmentioning
confidence: 91%
“…Both Hr −/− and SKH-1 animals exhibited significantly lower levels of Hr mRNA that equaled an ∼70% decrease in expression (Figure 1). Our previous work showed that Hr is expressed in suprabasal kerationcytes [19], [20] and is involved in the early UV response mechanism in primary human kerationcytes [29]. Therefore, we decided to focus our future experiments on the epidermis.…”
Section: Resultsmentioning
confidence: 99%
“…We also examined ODC expression in the converse situation when HR expression is significantly decreased due to a naturally occurring 22‐bp deletion in exon (hereafter referred to as HR keratinocytes) . As expected from the overexpression of HR , ODC expression in HR keratinocytes is significantly upregulated by approximately 2.5 times as compared to NHKs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, the HR mutant animals exhibit a coordinated loss of hair indicating an active process is at work while the SSAT‐TG mutants abnormally retain their club hair fibres and only shed them after mechanical stimulation, which accounts for the apparent random and individualized hair loss in the SSAT‐TG population. HR mutations are primarily considered to lead to dysregulated apoptosis and proliferation , and the downregulation of the HR undoubtedly accounts for the defective club hair formation seen in the SSAT‐TG animals. However, we hypothesize that the lack of active hair shedding is due to one of the many other pathways that putrescine effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation